Marine silicate weathering in the anoxic sediment of the Ulleung Basin: Evidence and consequences. (27th August 2016) - Kim, Ji‐Hoon; Torres, Marta E.; Haley, Brian A.; Ryu, Jong‐Sik; Park, Myong‐Ho; Hong, Wei‐Li; Choi, Jiyoung
Abstract: Marine silicate weathering (MSiW) in anoxic sediments has been recently shown to be a significant sink for CO2 generated by methanogenesis. Independently, the roles of clay dehydration (illitization) in producing water and driving upward fluid advection have been well established in deep marine sediments, but to date the K + source required for the reaction has not been established. Here we present chemical and strontium isotope properties of pore fluids from seven cores in the Ulleung Basin, which show radiogenic 87 Sr/ 86 Sr values (up to ∼0.71045), very high alkalinity values (maximum ∼130 mM), and enrichment in H4 SiO4, Na +, K +, and Mg 2+, consistent with MSiW. This reaction consumes CO2, generates alkalinity, and acts as a K + source for illitization; water released from MSiW‐supported illitization drives upward fluid flow. Our results highlight the importance of MSiW along continental margins and its underappreciated role in carbon cycling, silicate diagenesis, and hydrogeology of marine systems. Key Points: High 87 Sr/ 86 Sr, alkalinity, and dissolved cations in pore fluids reveal silicate weathering Marine silicate weathering serves as the K + source for illitization at depth Marine silicate weathering consumes CO2 generated by methanogenesis and generates alkalinity